The Role of Service Quality in Increasing Customer Satisfaction and Loyalty: An Analysis of BNI Mobile Banking - Muhammad Taqi Ardabilli; Muinah Fadhilah; Ambar Lukitaningsih (Dinasti Publisher, 2024)
The rapid evolution of digital business necessitates adaptation. This study examines how service quality influences customer satisfaction and loyalty among BNI Mobile Banking users. A quantitative approach was employed to analyze 125 active BNI Mobile Banking customers with at least 5 million rupiah in savings and under 60 years old from the BNI KCP Ampel branch. Path analysis using Smart PLS 4.0 software was conducted to determine the relationships between service quality dimensions (assurance, convenience, reliability, efficiency) and customer satisfaction and loyalty. Results indicate that assurance, convenience, and reliability positively impact satisfaction, which in turn positively affects loyalty. While satisfaction mediates the influence of assurance and reliability on loyalty, it does not mediate the effects of comfort, efficiency, and convenience on loyalty. Essentially, the study found that improving assurance, convenience, and reliability of BNI Mobile Banking can enhance customer satisfaction, leading to increased loyalty. However, comfort, efficiency, and convenience directly impact loyalty without being mediated by satisfaction.